2010
DOI: 10.1160/th09-10-0723
|View full text |Cite
|
Sign up to set email alerts
|

Investigating clearance mechanisms for recombinant activated factor VII in a perfused liver model

Abstract: Clearance mechanisms for recombinant activated human FVII (rFVIIa; NovoSeven), a heterogeneously glycosylated protein, have yet to be fully elucidated, but may involve the liver. The effects of the gamma-carboxy glutamic acid (Gla) domain and the sialic acid content of the protein on rFVIIa clearance were investigated following intravenous administration of rFVIIa lacking the Gla domain, des(1-44) rFVIIa and asialo-rFVIIa in pharmacokinetic (PK) studies and perfused rat livers. PK parameters for both rFVIIa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The inability of RAP to completely abolish endocytosis of 125 I-rFVIIa suggests that receptors other than megalin and cubilin may also be involved. ASGPR has been reported to be expressed in human proximal tubules [42] and is suggested to have a role in the clearance of rFVIIa in a perfused liver model [17]. However, it does not appear to play a role in endocytosis of rFVIIa in the OK cells as an excess of ASOR was unable to reduce endocytosis of 125 I-rFVIIa (fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inability of RAP to completely abolish endocytosis of 125 I-rFVIIa suggests that receptors other than megalin and cubilin may also be involved. ASGPR has been reported to be expressed in human proximal tubules [42] and is suggested to have a role in the clearance of rFVIIa in a perfused liver model [17]. However, it does not appear to play a role in endocytosis of rFVIIa in the OK cells as an excess of ASOR was unable to reduce endocytosis of 125 I-rFVIIa (fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that rFVIIa, following intravenous administration in rats, is cleared and distributed into endosomes and lysosomes within hepatocytes and sinusoidal Kupffer cells [16]. In an in situ perfused rat liver, at least one clearance mechanism has been suggested, involving clearance of a subpopulation of rFVIIa, based on the unsialylated N-terminal carbohydrate moieties [17]. To our knowledge, little data are available about the specific in vivo clearance mechanisms of injected rFVIIa in catabolic organs other than the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Asialo rFVIIa clears quickest, whereas pdFVII, having a higher degree of sialylation, is cleared to a lesser extent [1]. In the case of FIX, the degrees of serine phosphorylation and tyrosine sulfation in the activation peptide have been postulated to influence pharmacokinetic behavior, especially in vivo recovery [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the impact of glycosylation on the PK behavior of mAbs was also investigated among these years, especially for terminal sialic acid. It is found that the sialylation degree of a glycoprotein can play a significant role in the serum half-life353637. Glycoproteins can be removed from the circulation via a sugar-based interaction with ASGPRs on hepatic cells373839.…”
mentioning
confidence: 99%
“…Glycoproteins can be removed from the circulation via a sugar-based interaction with ASGPRs on hepatic cells373839. Several studies have reported that the ASGPRs induced endocytosis can lead to the clearance of glycoproteins in circulation364041. Sialic acid content varies depending on several factors including cell types and fermentation process, all these factors can result in different terminal sugar moieties of mAbs.…”
mentioning
confidence: 99%